Preventable statin adverse reactions and therapy discontinuation. What can we learn from the spontaneous reporting system?. Issue 5 (4th May 2018) - Sessa, Maurizio; Rafaniello, Concetta; Scavone, Cristina; Mascolo, Annamaria; di Mauro, Gabriella; Fucile, Annamaria; Rossi, Francesco; Sportiello, Liberata; Capuano, Annalisa
ABSTRACT: Background : Statin treatment is often associated with poor adherence, which may be due to the onset of adverse drug reactions (ADRs). We investigated on potential risk factors related to preventable cases of statin-induced ADRs and to the discontinuation of statin therapy. Methods : We performed a study using the database of Italian spontaneous reporting. The target population for the preventability assessment was all patients with suspected statin-induced ADRs deriving from Campania Region (a territory of Southern Italy) between 2012 and 2017. Additionally, a local sentinel surveillance site involving General Practitioners was selected to countercheck in routine clinical practice the role of ADRs for statin discontinuation. Results : In total, 34 of 655 (5.19%) regional cases were preventable and among detected risk factors 90.0% was related to healthcare professionals' practices and 10.0% to patient behaviour. In 81.4% (533/655) of cases, statin therapy was discontinued due to ADRs, mainly classified as not serious and associated with a positive prognosis. These results were also confirmed in the active sentinel site. Conclusions : Our findings suggest an inappropriate use of statins among the identified preventable cases and a potential inappropriate statin discontinuation due to ADRs. These factors may be useful for targeting interventions to improve statin adherence.